2007
DOI: 10.1111/j.1475-6765.2007.00697.x
|View full text |Cite
|
Sign up to set email alerts
|

New regionalism in five Swiss metropolitan areas: An assessment of inclusiveness, deliberation and democratic accountability

Abstract: Abstract.  Focusing on area‐wide policy coordination in metropolitan areas, this article examines the democratic consequences of the supposed shift ‘from government to governance’. In the first, theoretical, part it draws upon the debate on old and new routes towards regionalism in order to identify four different types of metropolitan governance. It then develops two working hypotheses – an optimistic and a pessimistic one – in order to analyse the implications of various types of metropolitan governance on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 30 publications
1
42
0
4
Order By: Relevance
“…Unlike representative institutions, there is no statutory right for public scrutiny with respect to decision-making bodies of governance networks. Case studies of drug policy, public transport, cultural policy, and water provision have shown that lines of accountability are blurred in governance networks (Kübler & Schwab, 2007). The budgetary process seems to provide the main link for connecting governance networks to both elected politicians in representative institutions as well as the electorate through direct democratic instruments (Wälti, Kübler, & Papadopoulos, 2004).…”
Section: The Power Of Elected Politicians In Governance Networkmentioning
confidence: 99%
“…Unlike representative institutions, there is no statutory right for public scrutiny with respect to decision-making bodies of governance networks. Case studies of drug policy, public transport, cultural policy, and water provision have shown that lines of accountability are blurred in governance networks (Kübler & Schwab, 2007). The budgetary process seems to provide the main link for connecting governance networks to both elected politicians in representative institutions as well as the electorate through direct democratic instruments (Wälti, Kübler, & Papadopoulos, 2004).…”
Section: The Power Of Elected Politicians In Governance Networkmentioning
confidence: 99%
“…The conducted case studies, however, do not clearly support either the pessimistic or the optimistic view. The results imply that the question of democracy is probably less dependent on the types of metropolitan governance than on other-not yet identifiedfactors (Kübler and Schwab 2007). 6.…”
Section: Notesmentioning
confidence: 82%
“…2. The distinctions between "the new regionalism" and the earlier public choice and "old regionalism" approaches are well documented elsewhere (see Frisken and Norris 2001;Kubler and Schwab 2007). 3.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 96%